Pharmacokinetics in drug development. Volume 3 Advances and applications - Bonate, Peter L.; Howard, Danny R.; SpringerLink (Online service). (New York Springer, 2011)
No back cover text.
Modeling Tumor Growth in Oncology -- Drug-Drug Interactions: Designing Development Programs and Appropriate Product Labeling -- Modeling the Progression of Disease -- The Use of Dried Blood Spots for Concentration Assessment in Pharmacokinetic Evaluations -- Microdosing: Pharmacokinetic and Metabolism Data Early in the Drug Development Process -- Metabolite Testing in Drug Development -- The - Omics in Drug Development -- Optimal Design of Pharmacokinetic-Pharmacodynamic Studies -- Pharmacokinetic Studies in Pregnant Women -- Design, Conduct and Analysis of Thorough QT Studies -- Contribution of Quantitative Whole-body Autoradioluminography to the Early Selection and Development of Drug Candidates -- Pharmacokinetics, Modeling, and Simulation in the Development of Sunitinib Malate: A Case Study -- The Clinical Significance of Drug Transporters in Drug Disposition and Drug Interactions.
Electronic reproduction.
Keywords: Pharmacokinetics; Drugs -- Design; Pharmaceutical technology; Biotechnology; Electronic books